Edward Scott The Last of the English Dancing Masters - Buckland, Theresa Jill (Edinburgh: Edinburgh University Press, 2003)
RESUMEN: From the medieval period to the early twentieth century, fashionable European dance culture was quietly dominated by the figure of the dancing master. For several centuries, he had played a pivotal role in crossing the terrains of theatre, court and the wider social sphere, disseminating and sometimes creating new dance fashions while acting as advocate for the social, artistic and historical value of the art of dancing. His slow decline in influence was finally marked by the complete severance of the technique of social dancing from its basis in ballet during the early 1900s. Instead of the turned-out foot positions and melodic musical accompaniment of the old European style, a more democratized dancing public sought and accessible mode of dancing, enlivened by the syncopation of African-American rhythms. Although efforts were made in England, after the First World War, to infuse the new with the old, popular acceptance of the jazz age in dance and music, sounded the death knell of the Victorian dancing master. Parallel to dance as a theatre art, social dancing in the late Victorian and Edwardian era was irreversibly separated from established traditions. In the analyses of dance from this period, much of the existing scholarship has tended to focus upon innovators and their revolutionary contributions, often interpreted within the context of modernism and modernity. Whereas such an approach is fundamental to the understanding and appreciation of dance history and contemporary performance, there is also a twofold case to be made, I believe, for looking at continuities and traditions. Firstly, though analysis of the "old guard", so to speak, greater contextual light may be shed on innovative figures on order to appraise more fully the extent and significance of their achievements. Secondly, the process may also allow some reevaluation of persons thought to be, or ignored as, irrelevant to the development of dance as understood in contemporary Europe and North America